The mitochondrial deoxyguanosine kinase is required for cancer cell stemness in lung adenocarcinoma - Shengchen Lin; Chongbiao Huang; Jianwei Sun; Oana Bollt; Xiuchao Wang; Eric Martine; Jiaxin Kang; Matthew D Taylor; Bin Fang; Pankaj K Singh; John Koomen; Jihui Hao; et al. (EMBO Molecular Medicine)
Abstract The mitochondrial deoxynucleotide triphosphate (dNTP) is maintained by the mitochondrial deoxynucleoside salvage pathway and dedicated for the mtDNA homeostasis, and the mitochondrial deoxyguanosine kinase (DGUOK) is a rate‐limiting enzyme in this pathway. Here, we investigated the role of the DGUOK in the self‐renewal of lung cancer stem‐like cells (CSC). Our data support that DGUOK overexpression strongly correlates with cancer progression and patient survival. The depletion of DGUOK robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self‐renewal. Mechanistically, DGUOK is required for the biogenesis of respiratory complex I and mitochondrial OXPHOS, which in turn regulates CSC self‐renewal through AMPK‐YAP1 signaling. The restoration of mitochondrial OXPHOS in DGUOK KO lung cancer cells using NDI1 was able to prevent AMPK‐mediated phosphorylation of YAP and to rescue CSC stemness. Genetic targeting of DGUOK using doxycycline‐inducible CRISPR/Cas9 was able to markedly induce tumor regression. Our findings reveal a novel role for mitochondrial dNTP metabolism in lung cancer tumor growth and progression, and implicate that the mitochondrial deoxynucleotide salvage pathway could be potentially targeted to prevent CSC‐mediated therapy resistance and metastatic recurrence.